Mobile Payment Usage: Risk Perspective - Atika Vitrizky Puspitaningrum; Aflit Nuryulia Praswati; Helmia Khalifah Sina (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2023)
Pandemic risks create a lot of worries for consumers when making purchase transactions. When the need for a product increases even though movement restrictions are still enforced by the government, the existence of mobile payments is one of the solutions offered to consumers. This research takes a deeper look at the behavior of using mobile payments during a pandemic. This study uses the Smart PLS analysis tool to process data that has been collected by a total of 100 respondents. The results obtained are that readiness to adopt mobile payments has a positive effect on the use of mobile payments, perceptions of the risk of a pandemic have a positive but not significant effect on the use of mobile payments. Meanwhile, it turns out that consumers who use mobile payments.The behavior of using Mobile Payment mediated has a significant positive influence on Adoption Readiness on EWOM. The behavior of Using Mobile Payment mediated has a positive influence on Perception of Risk to EWOM significantly. This research is still limited to consumers' views regarding risk and has not examined other variables that may influence mobile payment usage behavior. So that further research can use a different point of view regarding the reasons for using mobile payments. There is even a phenomenon of having more than one mobile payment account